Comparing Uterine Electromyography & Tocodynamometer to Intrauterine Pressure Catheter for Monitoring Labor - Sangeeta, Jain; Antonio, F. Saad; Sanmaan, S. Basraon (Journal of Women's Reproductive Health, 2016)
Objective The tocodynamometer (TOCO) has poor sensitivity and specificity in monitoring uterine contractions, especially in obese patients. The intrauterine pressure catheter (IUPC) can be used to monitor adequacy of contractions, but only after amniotomy. Transabdominal uterine electromyography (EMG) and the TOCO were compared to the gold standard IUPC for monitoring uterine contractions. Methods Forty term pregnant women in labor with ruptured membranes were consented for this study. The root mean square (RMS) plot from EMG signals was compared to IUPC and TOCO recordings for 20 to 40 minutes. A comparison between the total contraction number, frequency, and the difference in contraction peak time was made using Student-t test or ANOVA (P<0.05 was significant). Results There was no significant difference in the contraction number and frequency when comparing the RMS, TOCO, and IUPC. The paper tracings had a greater standard deviation (8.57) than the digitally saved data (3.93). The mean peak time difference between TOCO and IUPC was 0.74 seconds (P=0.78; SD 5.2). For RMS vs. IUPC peaks, the mean peak difference between was 0.13 seconds (P=0.95; SD 3.93). Conclusions Uterine electrical activity measured with transabdominal uterine EMG may be used to monitor labor in patients as an alternative to the TOCO and the IUPC.
Keywords: contraction peak time; intrauterine pressure catheter; tocodynamometer; uterine electromyography